Marshall Performance and Volumetric Properties of Styrene-Butadiene-Styrene Modified Asphalt Mixtures - Sameer Abbas Jasim; Mohammed Qadir Ismael (Civil Engineering Journal, 2021)
The durability of asphalt pavement is associated with the properties and performance of the binder. This work-study intended to understand the impact of blending Styrene-Butadiene-Styrene (SBS) to conventional asphalt concrete mixtures and calculating the Optimum Asphalt Content (OAC) for conventional mixture also; compare the performance between SBS modified with the conventional mixture. Two different kinds of asphalt penetration grades, A.C. (40-50) and A.C. (60-70), were improved with 2.5 and 3.5% SBS polymer, respectively. Marshall properties were determined in this work. Optimum Asphalt Content (OAC) was 4.93 and 5.1% by weight of mixture for A.C. (40-50) and (60-70), respectively. Marshall properties results show an increasement in the stability value by 8.65 and 20.19% for A.C. (40-50) with 2.5 and 3.5% of SBS, respectively. And an increasement by 9.32 and 20.61% for AC (60-70) with 2.5 and 3.5% of SBS respectively. Furthermore, the results indicate a decrease in Marshall flow by 14.7 and 26.47% for A.C. (40-50) with 2.5 and 3.5% SBS respectively and a decrease by 10.46 and 21.21% for A.C. (60-70) with 2.5 and 3.5% SBS respectively. Other Marshall properties were also calculated. Moreover, Blending SBS polymers to conventional asphalt mixtures produces a better performance to asphalt binder and better Marshall properties, which provides a great solution to Iraqi road problems affected by temperature and high traffic load, including less maintenance. Doi: 10.28991/cej-2021-03091709 Full Text: PDF